A formação e atuação do psicólogo junto à pessoa com deficiência intelectual sob o impacto da desvalorização do conhecimento - Mezzomo, Rafaela (2012)
This study was focused on the formation and work of the psychologist in Special Education with students who have intellectual disabilities and are enrolled in units of APAE - Association of Parents and Friends of Exceptional - and can feel the impact of the depreciation of knowledge on contemporan society. The objective was determine what kind of knowledge is being taught on Special Education, and about people with intellectual disabilities on the period which psychologists, who works in this area, were in training, or can we say, in graduation. This search is a literature review and empirical. In research literature performed, at first, an overview of authors discussing the development of psychology as a science and the entry of Psychology at school, trying to understand the activities of the school psychology. Then we tried to talk about the neoliberal ideologies and their interfaces modern schools, finding what kind of knowledge is disseminated within the education of individuals. In this sense, we learned from studies of Vygotski on defectology to understand the development of disabled people, and seek a psychological theory that overcomes the widespread view on the noneducability of deficient. Finally we performed a brief recovery of Special Education in Brazil and the policies aimed to care for individuals with disabilities. The empirical research involved ten psychologists working in seven special schools for intellectually disabled, located in seven cities in the interior of Paraná. Data were collected through semi-structured interview technique, based on a script composed with six questions. The information obtained through interviews were analysed and discussed from the literature research, seeking to highlight contradictions through the exercise of historical materialism. The results showed that, for the most part, psychologists use assessment technique and testing application that isolate the people with intellectual disability, and the same time, understand that is necessary to carry out, activities tailored to the abilities of their students. The psychologists saw their training was inadequate, because they were not covered with more specific knowledge about Special Education and the work of psychologists in this area. We conclude that the training in psychology under the Special Education is impacted by the fact that modern society devalue the knowledge, because, according to the ideology disseminated by neoliberalism, individuals are solely responsible for their learning and development, becoming relegated the value of knowledge produced by humanity in generation before us.